The Effect of Exports and Investment on Economic Growth in North Sumatra - Khairani Matondang; Revita Yuni; Nur Aulia Pratiwi; Laili Hasmiyah Harahap (Outline Journal of Economic Studies, 2026)
Purpose: This study aims to determine and analyze the effect of exports and investment on economic growth in North Sumatra Province. Methods: This research uses secondary data obtained from the Central Bureau of Statistics (BPS) of North Sumatra Province for the 2001–2020 period. The analysis examines the relationship between exports and investment as independent variables and economic growth as the dependent variable, measured by Gross Regional Domestic Product (GRDP). Results: The results show that exports have a positive and significant effect on economic growth in North Sumatra Province. Investment also has a positive and significant effect on economic growth. Simultaneously, exports and investment significantly influence economic growth. The findings further indicate that exports and investment contribute 94% to economic growth in the province. Conclusion: Exports and investment play an important role in supporting economic growth in North Sumatra Province. Increasing export performance and investment levels can significantly enhance regional economic development. Originality/value: This study provides empirical evidence of the strong contribution of exports and investment to economic growth in North Sumatra Province using a 20-year observation period, highlighting their dominant role in regional economic development.